Language Preservation Practices in Nepal - Adhikari, Rishiram (Nepal Journal of Multidisciplinary Research, 2022)
Preserving endangered language is one of the challenging tasks for the governments of the world. Day by day endangered languages are declining from the world due to various reasons. In the context of Nepal, some of the endangered languages are going to loss with changing socio economic and cultural situation. The study focused on language preservation practices of Nepal in term of legal and constitutional provisions and its implication. Policy formulation is not only sufficient for preserving endangered languages because implementation mechanisms cannot effectively function in developing and under developed nation like Nepal. The study followed qualitative research design and analyzed the issue related to language preservation policy and practices. By analyzing both primary and secondary data collected from different sources showed that language preservation practice cannot properly function in Nepal due to lack of resources, commitment of authority and influenced of global and national language.